Vasodilator-Stimulated Phosphoprotein Biomarkers Are Associated with Invasion and Metastasis in Colorectal Cancer - Pitari, Giovanni M (Biomark Cancer, 2018)
BACKGROUND AND AIMS: The benefit of adjuvant chemotherapy for stage II colorectal cancer (CRC) patients remains unclear, emphasizing the need for improved prognostic biomarkers to identify patients at risk of metastatic recurrence. To address this unmet clinical need, we examined the expression and phosphorylation status of the vasodilator-stimulated phosphoprotein (VASP) in CRC tumor progression. VASP, a processive actin polymerase, promotes the formation of invasive membrane structures leading to extracellular matrix remodeling and tumor invasion. Phosphorylation of VASP serine (Ser) residues 157 and 239 regulate VASP function, directing subcellular localization and inhibiting actin polymerization, respectively. METHODS: The expression levels of VASP protein, pSer(157)-VASP, and pSer(239)-VASP were determined by immunohistochemistry in tumors and matched normal adjacent tissue from 141 CRC patients, divided into 2 cohorts, and the association of VASP biomarker expression with clinicopathologic features and disease recurrence was examined. RESULTS: We report that changes in VASP expression and phosphorylation were significantly associated with tumor invasion and disease recurrence. Furthermore, we disclose a novel 2-tiered methodology to maximize VASP positive and negative predictive value performance for prognostication. CONCLUSION: VASP biomarkers may serve as prognostic biomarkers in CRC and should be evaluated in a larger clinical study.